Pandangan Dunia Pengarang dalam Novel Pulang Karya Tere Liye - Ricky Daliuwa; Ellyana Hinta; Herson Kadir (Ideas Publishing, 2023)
This study aims to describe the structural elements and the author's world view in the novel Pulang by Tere Liye. The data analysis technique uses the dialectical method which is a type of research in the sociology of literature through a genetic structuralism approach. The results of the study present an explanation of the structural elements of the novel Pulang by Tere Liye in the form of identifying the intrinsic elements (plot, characters, characterizations, setting, point of view, and themes) and the extrinsic elements of the novel (socio-economic background), the author's social life related to the novel ( background of personality, education, culture, and experience), and views of Tere Liye as the author of the novel Pulang (the reality of the shadow economy, the reality of domination and hegemony, moral and moral awareness, and the importance of education and family).